2013
DOI: 10.1016/j.envpol.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Characterising metal build-up on urban road surfaces

Abstract: Reliable approaches for predicting pollutant build-up are essential for accurate urban stormwater quality modelling. Based on the in-depth investigation of metal build-up on residential road surfaces, this paper presents empirical models for predicting metal loads on these surfaces. The study investigated metals commonly present in the urban environment. Analysis undertaken found that the build-up process for metals primarily originating from anthropogenic (copper and zinc) and geogenic (aluminium, calcium, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 11 publications
1
38
1
2
Order By: Relevance
“…It is noteworthy that the results were not consistent with previous findings stating that the pollutant wash-off has a great impact on pollutant load present in runoff, while pollutant build-up has only a minor effect [8,[20][21][22]. The possible reason for these different observations could be related to the specific size of accumulated solids.…”
Section: Figure 5 Effect Of Antecedent Dry Days On Washed-off Total contrasting
confidence: 56%
See 1 more Smart Citation
“…It is noteworthy that the results were not consistent with previous findings stating that the pollutant wash-off has a great impact on pollutant load present in runoff, while pollutant build-up has only a minor effect [8,[20][21][22]. The possible reason for these different observations could be related to the specific size of accumulated solids.…”
Section: Figure 5 Effect Of Antecedent Dry Days On Washed-off Total contrasting
confidence: 56%
“…Vaze and Chiew [8] found that particles less than 300 μm were predominant in their place of study; Egodawatta and Goonetilleke [20] noted that particles finer than 100 μm had the largest fraction on studied pavements, and Wijesiri et al [22] studied that the greatest wash-off load was composed mainly of particle size fractions less than 150 μm. Among these studies, the predominant particles were relatively coarser than those of the present study.…”
Section: Figure 5 Effect Of Antecedent Dry Days On Washed-off Total mentioning
confidence: 99%
“…Typically the values of b are negative (Egodawatta et al, 2013) indicating that during dry conditions the build-up process decreases gradually after an initial high accumulation and eventually reaches an almost constant value after 14 days. This predicted enhanced early build-up combined with the amounts of material which can potentially be deposited on surfaces similar to those found in car parks indicate the need for regular cleaning to ensure the effective removal of pollutants, particularly those associated with coarse solids.…”
Section: Accumulation Modelling Processesmentioning
confidence: 99%
“…A wide range of mathematical models including linear, power, exponential and MichaelisMenton functions have been used to describe the temporal build-up process (Huber and Dickinson 1988). However, the most widely employed predictive relationships for urban surfaces are the exponential (Bertrand-Krajewski et al, 1993;Charbeneau and Barrett, 1998;Deletic et al, 1997;Shaheen, 1975) and power functions (Ball et al, 1998;Egodawatta et al, 2013).…”
Section: Accumulation Modelling Processesmentioning
confidence: 99%
“…However, only limited actual direct measurements of RDS build-up are available, and it has instead been inferred from the measurements of RDS wash-off (Pitt et al, 2004;Shaw et al, 2006;Vaze and Chiew, 2002). In recent years, a few studies have revealed that RDS build-up is influenced by antecedent dry periods, rainfall events and street sweeping (Deletic and Orr, 2005;Egodawatta et al, 2013;Shen et al, 2016;Tian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%